“I just don’t feel …. Worthy”: A qualitative investigation of the relationship between social media and self-esteem in young adult South African women - Breedt, Catherine (The IIE, 2020)
From a South African perspective, there is a lack of knowledge involving the relationship between social media and self-esteem in young adult women. In an era where the use of social media influences many aspects of daily life, it is important to understand consequences of social media and how it influences self-esteem. Furthermore, large amounts of time are spent on various social media platforms such as Facebook and Instagram where engagement with others becomes of great importance (Bergagna & Tartaglia, 2018). The present study made use of a qualitative research design, and online semi structured interviews via Skype were conducted in order to maintain the safety of the participants and researcher during the Covid-19 pandemic. Three young adult women between the ages of 19 and 35 years who resided in Durban were interviewed and comprised the sample used in this study and thereafter, data collected was analysed thematically. The findings illustrated that a relationship exists between social media and selfesteem in young adult South African women. The nature of the relationship, positive and negative, is dependent on the content that is engaged with at any given time. Content that surrounds the ideal body image has a negative influence on self-esteem and participants reported having a low self-esteem after engaging with content. A recommendation for future studies would be to use a larger sample to gather a wider range of data.
Keywords: Worthiness; Social media; Self-esteem; Young adult women; Perceptions of worth